Drop of Indigo Dye - Husain, Aisha (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2025)
I share my story of how an unexpected diagnosis changed my lens in caring for my patients. This story shines a light on how narrative medicine tools employed by various healthcare professionals touch me as a patient, in turn, realizing how it trickled down to strengthen relationships with my patients as their comprehensive family physician. Narrative medicine permitted me to process my health journey and re-assess my values to gain new insights on how I derive meaning and purpose.